Nilai Sosial Dalam Novel Seteru 1 Guru Karya Haris Priyatna: Tinjauan Sosiologi Sastra Dan Implementasinya Sebagai Bahan Ajar Sastra Indonesia Di SMP N 6 Boyolali - Purnomo, Arif Joko, Drs. Zainal Arifin, M.Hum (2016)
The purpose of this study was to describe the structure of the novel builders Seteru 1 Guru by HarisPriyatna, the social value of the novel Seteru 1 Guru, the implementation of the social value of literature as teaching materials. This study used a qualitative descriptive approach. The data source of the novel.Data collection techniques using literature techniques, see and record.Mechanical validity of the data using triangulation data. Data were analyzed using the dialectical method. The analysis showed that:(1) the structure of the novel builders Seteru 1 Guru made up the story themes of friendship into enmity. Facts story:the story line groove mix. Figures that Tjokroaminoto, Sukarno, Musso, and Kartosoewirjo.Background place in the novel, Surabaya, Blitar, Bandung, KebonJati, Sluisbrugstraat, Solo, Ponorogo, and Jakarta. (2) social value of the novel Seteru 1 Guru consists of the value of compassion, the value of responsibility, and the value of life harmony. Value affection consists of devotion, mutual help, the family, and caring. (3) the social value of the novel Seteru 1 Guru works HarisPriyatnta can be used as teaching materials Indonesian literature in junior high. The results are used as teaching materials in the form of handouts. Keywords: social values, sociology of literature, novels Seteru 1 Guru,implementation of research results in teaching literature.